Global research priorities to mitigate plastic pollution impacts on marine wildlife - Vegter, AC; Barletta, M; Beck, C; Borrero, J; Burton, H; Campbell, ML; Costa, MF; Eriksen, M; Eriksson, C; Estrades, A; Gilardi, KVK; Hardesty, BD; et al. (Endangered species research, 2014)
Marine wildlife faces a growing number of threats across the globe, and the survival of many species and populations will be dependent on conservation action. One threat in particular that has emerged over the last 4 decades is the pollution of oceanic and coastal habitats with plastic debris. The increased occurrence of plastics in marine ecosystems mirrors the increased prevalence of plastics in society, and reflects the high durability and persistence of plastics in the environment. In an effort to guide future research and assist mitigation approaches to marine conservation, we have generated a list of 16 priority research questions based on the expert opinions of 26 researchers from around the world, whose research expertise spans several disciplines, and covers each of the world's oceans and the taxa most at risk from plastic pollution. This paper highlights a growing concern related to threats posed to marine wildlife from microplastics and fragmented debris, the need for data at scales relevant to management, and the urgent need to develop interdisciplinary research and management partnerships to limit the release of plastics into the environment and curb the future impacts of plastic pollution.